IMPLEMENTASI KEBIJAKAN PROGRAM KELUARGA HARAPAN (PKH): STUDI KASUS RT 14, KARANGWARU, TEGALREJO, KOTA YOGYAKARTA - Ika Wijayanti; Triya Meilina; Maria Florentina Dhiu; Putri Wening Larasati Purwaningsih; Randi Basri Sattu (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
PKH is a conditional social assistance program aimed at poor families with the goal of improving education, health, and social welfare. The implementation of PKH in RT 14, Karangwaru Village, Tegalrejo District, Yogyakarta City is analyzed using George C. Edward III's policy implementation model, which includes four main variables: communication, resources, disposition, and bureaucratic structure. The research was conducted using a descriptive method within a qualitative approach. The results indicate that effective communication between social assistants and the Beneficiary Families (KPM) ensured clear understanding of the assistance program. Resources, such as competent assistants and adequate facilities, support the smooth implementation of the program. A positive disposition from social assistants and local officials contributes to the success of PKH, although there are still coordination issues and task fragmentation among different parties, especially at the RT level. Although the implementation of PKH in RT 14 runs well, coordination between agencies and task distribution needs to be improved to enhance the program's effectiveness in the future..